Policy Learning and the Diffusion of Stand‐Your‐Ground Laws. Issue 3 (5th June 2015) - Butz, Adam M.; Fix, Michael P.; Mitchell, Joshua L.
<x xml:space="preserve">Abstract</x> Stand‐Your‐Ground (SYG) laws have recently received increased attention due to the controversial verdict in the 2013 George Zimmerman trial. At the time of the trial, 22 states had adopted SYG laws, with Florida adopting the first SYG law only a few years earlier. This article explores how policy learning contributed to the diffusion of these laws among U.S. states. It is found that learning exhibits atypical and complex patterns of diffusion not observed in previous studies. We posit that this dynamic is likely attributed to the fact that SYG is a controversial version of a morality policy, and these types of policies may exhibit multiple properties of policy learning theory. In addition, we find that multiple internal determinants including racial context, gun purchase rates, and poverty influence the likelihood of SYG adoption. Related Articles <mixed-citation id="polp12116-cit-0061" publication-type="journal" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <string-name> <surname>Tucker</surname>, <given-names>Justin A.</given-names></string-name>, <string-name><given-names>James W.</given-names><surname>Stoutenborough</surname></string-name>, and <string-name><given-names>Mathew R.</given-names><surname>Beverlin</surname></string-name>. <year>2012</year>. " Geographic Proximity in the Diffusion of Concealed Weapons Permit Laws ." <source content-type="journalTitle">Politics & Policy</source><volume>40</volume>: <fpage>1081</fpage>–<lpage>1105</lpage>. http://onlinelibrary.wiley.com/doi/10.1111/j.1747-1346.2012.00399.x/abstract</mixed-citation> <mixed-citation id="polp12116-cit-0062" publication-type="journal" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <string-name> <surname>Shanahan</surname>, <given-names>Elizabeth A.</given-names></string-name>, <string-name><given-names>Mark K.</given-names><surname>McBeth</surname></string-name>, and <string-name><given-names>Paul L.</given-names><surname>Hathaway</surname></string-name>. <year>2011</year>. " Narrative Policy Framework: The Influence of Media Policy Narratives on Public Opinion ." <source content-type="journalTitle">Politics & Policy</source><volume>39</volume>: <fpage>373</fpage>–<lpage>400</lpage>. http://onlinelibrary.wiley.com/doi/10.1111/j.1747-1346.2011.00295.x/abstract</mixed-citation> <mixed-citation id="polp12116-cit-0063" publication-type="journal" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <string-name> <surname>Propheter</surname>, <given-names>Geoffrey</given-names></string-name>. <year>2012</year>. " Political Determinants of State E‐Commerce Sales Tax Policy ." <source content-type="journalTitle">Politics & Policy</source><volume>40</volume>: <fpage>657</fpage>–<lpage>679</lpage>. http://onlinelibrary.wiley.com/doi/10.1111/j.1747-1346.2012.00369.x/abstract</mixed-citation> Related Media <mixed-citation id="polp12116-cit-0064" publication-type="other" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <collab collab-type="groupName" xlink:type="simple">PBS Newshours</collab>. <year>2013</year>. "<source content-type="otherTitle">Americans Rally in Protest of Zimmerman Verdict</source>." http://video.pbs.org/video/2365046883/</mixed-citation> <mixed-citation id="polp12116-cit-0065" publication-type="other" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <collab collab-type="groupName" xlink:type="simple">C‐Span</collab>. <year>2012</year>. "<source content-type="otherTitle">Guns and Stand Your Ground Laws</source>." http://www.c-span.org/video/?c3548463/guns-stand-ground-law</mixed-citation>